Barriers and facilitators to interdisciplinary communication during consultations: a qualitative study - Jane L Holl; Julie Johnson; Audrey Lyndon; Pingyang Liu (BMJ Open)
Objective Communication failures between clinicians lead to poor patient outcomes. Critically injured patients have multiple injured organ systems and require complex multidisciplinary care from a wide range of healthcare professionals and communication failures are abundantly common. This study sought to determine barriers and facilitators to interdisciplinary communication between the consulting trauma, intensive care unit (ICU) team and specialty consultants for critically injured patients at an urban, safety-net, level 1 trauma centre.Design An observational qualitative study of barriers and facilitators to interdisciplinary communication.Setting We conducted observations of daily rounds in two trauma surgical ICUs and recorded the most frequently consulted teams.Participants Key informant interviews after presenting clinical vignettes as discussion prompts were conducted with a broad range of clinicians from the ICUs and physicians and nurse practitioners from the consultant teams who were identified during the observations. Interviews were recorded and transcribed verbatim. Data of these 10 interviews were combined with primary transcript data from prior study (25 interviews) and analysed together because of the same setting with same themes. Independent coding of the transcripts, with iterative reconciliation, was performed by two coders.Outcomes measures Facilitators and barriers of interdisciplinary communication were identified.Results A total of 35 interview transcripts were analysed. Cardiology and interventional radiology were the most frequently consulted teams. Consulting and consultant clinicians reported that perceived accessibility from the team seeking a consultation and the consultant team impacted interdisciplinary communication. Accessibility had a physical dimension as well as a psychological dimension. Accessibility was demonstrated by responsiveness between clinicians of different disciplines and in turn facilitated interdisciplinary communication. Social norms, cognitive biases, hierarchy and relationships were reported as both facilitators and barriers to accessibility, and therefore, interdisciplinary communication.Conclusion Accessibility impacted interdisciplinary communication between the consulting and the consultant team.Article summary Elucidates barriers and facilitators to interdisciplinary communication between consulting and consultant teams.